2020
DOI: 10.1108/jmp-09-2018-0398
|View full text |Cite
|
Sign up to set email alerts
|

Smile for the camera! The role of social presence and impression management in perceptions of technology-mediated interviews

Abstract: Purpose Videoconference interviews and asynchronous interviews are increasingly used to select applicants. However, recent research has found that technology-mediated interviews are less accepted by applicants compared to face-to-face (FTF) interviews. The reasons for these differences have not yet been clarified. Therefore, the purpose of this paper is to take a closer look at potential reasons that have been suggested in previous research. Design/methodology/approach The present study surveyed 154 working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
6
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(85 citation statements)
references
References 39 publications
6
70
6
3
Order By: Relevance
“…Furthermore, the picture of the interviewer contains only a part of the complete picture that can be seen in a FTF interview, which impairs non-verbal IM. In line with this, results from a recent survey by Basch et al (2020) concerning potential applicants' views of technology-mediated interviews revealed lower perceptions of being able to use IM in technology-mediated interviews.…”
Section: Ratings Of Interviewees' Performance In Ftf and Technology-mmentioning
confidence: 54%
See 4 more Smart Citations
“…Furthermore, the picture of the interviewer contains only a part of the complete picture that can be seen in a FTF interview, which impairs non-verbal IM. In line with this, results from a recent survey by Basch et al (2020) concerning potential applicants' views of technology-mediated interviews revealed lower perceptions of being able to use IM in technology-mediated interviews.…”
Section: Ratings Of Interviewees' Performance In Ftf and Technology-mmentioning
confidence: 54%
“…In addition, with regard to Gilliland's (1993) justice model, Sears et al also found that interviewees rated videoconference interviews not only lower regarding the possibility to present themselves, but rated them as less job-relevant and less face-valid. These results were paralleled in the survey by Basch et al (2020), which compared perceptions of FTF, videoconference, and asynchronous video interviews. In comparison to FTF interviews, fairness perceptions of videoconference interviews were lower and the difference was even stronger concerning the comparison of FTF versus asynchronous video interviews.…”
Section: Interviewees' Perceptions Of Different Interviewsmentioning
confidence: 69%
See 3 more Smart Citations